RATIONAL MANAGEMENT OF THE GENE POOL OF VALUABLE BREEDS OF ANIMALS FOR THE PURPOSE OF CONSERVATION OF BIOLOGICAL DIVERSITY - Murat B. Ulimbashev; Valery V. Kulintsev; Marina I. Selionova; Radina A. Ulimbasheva; Batyrkhan T. Abilov; Zhanna T. Alagirova (Юг России: экология, развитие, 2018)
Aim. The aim is to conduct an analysis of biodiversity of valuable breeds of animals, as well as to assess its condition, find ways of preserving domestic genetic resources and identify their economically valuable qualities. Discussion. The material is presented, which proves the need to preserve valuable, rare and endangered breeds of agricultural animals characterized by high quality indices of production, longevity, fertility, resistance to diseases, adaptive abilities to extreme environmental conditions. Importance of carrying out these measures is associated with the absorption of domestic flocks by foreign breeds, which led to a decrease in genetic diversity and the continuing trend in the displacement of rare and endangered breeds of animals. One of the ways of preserving animals that cause breeders' concern is the use of seed cryopreservation, which is actively pursued by a number of scientists and specialized institutions. Lack of effective legislative framework, as well as the lack of state support for conservation programs for these breeds, causes significant damage to the problem of preserving local breeds. Together with the listed benefits from breeding local livestock, their role in the biological diversity should be taken into account. Conclusion. Despite the invaluable contribution to the preservation of local breeds and animal populations made by the profile research institutes (the Federal Research Center for Animal Husbandry - L. K. Ernst Institute of Animal Husbandry, All Russian Research Institute Of Animal Breeding) and individual scientists, the given problem requires its inclusion in the legislative framework and effective state support.